Propuesta de mejora a los procesos de gestión proyectos i+d+i de la Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López - Coveña Bazurto, Evelyn Sofía (2020)
The present investigation was carried out with the objective of proposing improvements to the management processes of R + D + i projects of the Manabí Manuel Félix López Polytechnic School of Agriculture, for the improvement of their efficiency. Thus, scientific and legal theories were established that provided a theoretical basis for research, as well as scientific methods such as synthetic, inductive and deductive analytics that allowed the efficient development of activities where specific guidelines of management processes were examined. within the R&D projects to improve, where it was possible to establish through an interview that the processes are created through the institutional research system specifying the following subprocesses: call for projects; design and approval; registration and prioritization of and monitoring process of indicators to evaluate the execution of projects and their results. Subsequently, the respective valueadded analysis technique was applied to the selected scientific research subprocesses, determining that the subprocess of the R + D + i program and project management subprocess presents a poor value-added index as well as the review process and approval presented more inconvenience to the added value. Finally, with the results obtained, a proposal to the management processes of said department was determined, establishing the following actions: Focus training needs for the workers and servers of the institution, including activities for a better application of the corresponding process , include activities for a better application of the process, among others.